2019
DOI: 10.1080/19476337.2018.1564793
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical and antioxidant properties of gelatin-based films containing oily tomato extract (Solanum lycopersicum L.)

Abstract: View related articles View Crossmark data Citing articles: 7 View citing articles Physicochemical and antioxidant properties of gelatin-based films containing oily tomato extract (Solanum lycopersicum L.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 29 publications
(62 reference statements)
2
9
0
Order By: Relevance
“…According to this assay, films in this study show antioxidant activity in the range 200–900 μmol TE per mg of film. These results are similar to chitosan‐starch and gallic acid films, and higher than gelatin based films containing oily tomato extract and gelatin‐chitosan based films loaded with active compounds . The increase in antioxidant activity could be related to the exposure of residues during protein unfolding, a phenomenon that has previously been reported for proteins during ultrasonic pulses …”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…According to this assay, films in this study show antioxidant activity in the range 200–900 μmol TE per mg of film. These results are similar to chitosan‐starch and gallic acid films, and higher than gelatin based films containing oily tomato extract and gelatin‐chitosan based films loaded with active compounds . The increase in antioxidant activity could be related to the exposure of residues during protein unfolding, a phenomenon that has previously been reported for proteins during ultrasonic pulses …”
Section: Resultssupporting
confidence: 83%
“…These results are similar to chitosan-starch and gallic acid films, 23 and higher than gelatin based films containing oily tomato extract and gelatin-chitosan based films loaded with active compounds. 15,24 The increase in antioxidant activity could be related to the exposure of residues during protein unfolding, a phenomenon that has previously been reported for proteins during ultrasonic pulses. 22 The FRAP of the films showed significant differences between films (P < 0.05).…”
Section: Antioxidant Propertiesmentioning
confidence: 62%
“…A more intense reddish hue in the encapsulated MD:GA:TJ (3:1:14) with respect to MD:GA:TJ (1:3:14) confirms that it contained higher lycopene and β-carotene concentrations (Table 4). This is because lycopene and β-carotene are the pigments responsible for the red color of tomatoes (López-Palestina et al 2019;Raffo et al 2006;Rosales et al 2011). Similar behavior was reported by Quek et al (2007) and Oberoi and Sogi (2015), who evaluated the effect of MD concentration on pigments from watermelon juice.…”
Section: Tomato Juice Encapsulationsupporting
confidence: 75%
“…Some studies have reported that low-moisture powders present higher hygroscopicity values (Tonon et al 2008;Fernandes et al 2014), as could be observed in this research. In addition, the TJ is high in carotenoids that are of non-polar origin (Gutiérrez et al 2019;López-Palestina et al 2019) and therefore, the TJ absorbs less water. On the other hand, the hygroscopicity values reported in this study were like those found in studies in which MD:GA ratios of 3:1 and 1:1 were used to encapsulate bioactive compounds as anthocyanins from berry and sweet potato (Akhavan et al 2016;Mohd et al 2015).…”
Section: Tomato Juice Encapsulationmentioning
confidence: 99%
“…Water is an important component that has a significant effect on the physical properties and performance of packaging materials as well as on their microbial, chemical, and biochemical degradation. In biodegradable films, because of its hydrophilic nature, water interacts with these biopolymers through hydrogen bonds, resulting in an important plasticizing effect, , increasing the free volume and flexibility of the films. As a result, modifications on mechanical, permeability, and optical properties are expected. , Water can interact with the matrix components in different ways.…”
Section: Introductionmentioning
confidence: 99%